Lipid profile in psoriasis - Poudyal, Y; Rajbhandari, SL (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Psoriasis is a common inflammatory skin disorder. A predisposition to vascular occlusive disease and high prevalence of heart disease has been seen to be associated with psoriasis and it has been suggested that some of these patients have some disorders of lipid metabolism. Dyslipidemia has been suggested in the pathogenesis of this phenomenon. METHODS: One hundred and six patients were selected for the study. Among them 53 (male=26, female=27) with psoriasis were taken as case and 53 with other dermatologic diseases, after matching for age and sex, were taken as control. The lipid profile that comprised four parameters: serum HDL, LDL-C, TC and TG were determined for both case and control and compared. RESULTS: It was found that serum TG, TC levels were significantly higher and serum HDL level was significantly lower in patients with psoriasis (P<0.05). When the risk factors like alcoholism and smoking were adjusted, only abnormal serum level of TG and TC were seen to be significantly associated with psoriasis. CONCLUSION: This study showed that abnormal TG and TC are associated with psoriasis. This fact may be responsible for the high prevalence of cardiovascular events in psoriasis. It may be useful to do early screening and treatment of dyslipidemia to prevent the adverse cardiovascular event. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10485 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 16-19